Pemetaan penelitian information retrieval system menggunakan VOSviewer - Salsa Amalia Putri; Yunus Winoto; Rohanda Rohanda (Jurnal Informatio, 2023)
Information retrieval systems help filter information, so that the process of finding suitable information becomes fast and precise, but there are ways to find more effectively and efficiently with Information retrieval systems using bibliometric methods with the VOSviewer application. The research objectives are to map the trends of research results on the topic of information retrieval system in the library, to map the research results on the topic of information retrieval system in the library based on co-authorship, and to map the research results on the topic of information retrieval system in the library based on co-occurrence. The research method uses descriptive bibliometric analysis by using the Scopus scientific journal database. The results of research on the topic of information retrieval systems in libraries are fluctuating where the most research results occurred in 2008 with publications totaling 13 articles and the lowest publications were seen in 2010 and 2014 with only 1 article produced. The level of author productivity is at 13 authors who produce a total of 2 articles. Co-authorship analysis is useful to see the mapping of research topics through relationships or collaborations between authors. The number of authors analyzed is 278, of which there are only 13 authors who show relationships between other authors. Co-occurrence analysis is useful for displaying bibliometric networks between keywords in a visual form. There are 326 keywords taken and 18 keywords have an occurrence relationship. Based on the bibliometric analysis conducted, it can be seen the distribution of research topics related to information retrieval systems in libraries, including research keywords that are still rarely researched, such as metadata and user studies. This can be used as an opportunity for further research topics.